Media coverage of the violent crime in the Republic of Macedonia - Stefanovska Vesna (Temida, 2016)
Media is the main source of information about crime and the way it is displayed determines the position and public perception of this phenomenon. In addition to showing the commission of crime and its state, media are obliged to cover not only the activities of the criminal justice system within the framework of formal social control, but even more, the activities of civil society organizations and the Ombudsman as part of informal social control in combatting agaist crime. Because of the perception of their action, the questions that arise are: How the media understands the civil society and its role, how they transmit their public discourse, what they choose to publish, whom they protect, whom they marginalise and what message they send to the public? An analysis of these issues along with an analysis of current offenses is of particular importance in order to determine whether the media give a true or distorted picture of crime. Therefore, the aim of the paper is to present results of the survey of media coverage of violent crime in the Republic of Macedonia.